The Currency and Relevancy of Confucian Pedagogy in Doctoral Supervision - Vai Io Lo (Bond Law Review)
The training of future academics and researchers is part of higher education. Doctoral studies consist of both teaching and research. Numerous studies have been conducted on the theory and practice of doctoral studies in and across various disciplines. Basically, the central questions of doctoral supervision are why, what, and how. It is imperative for a prospective supervisor to understand why he or she would like to undertake doctoral supervision. This is because the underlying aims will affect the quality of the intellectual and research training experience for both the supervisor and the supervisee. Once the underlying reasons are identified, the next question is what the supervisor wants to achieve. In essence, what a supervisor would like to accomplish in doctoral supervision is a value judgement because to what he or she attaches importance determines the intended outcomes. Towards the specific goals, the supervisor must determine how to materialize them. In fact, what approach or style as well as what policies and strategies should be adopted to cultivate research and scholarship skills in doctoral students constitute a significant portion of existing literature. Given that the ‘how’ is the most challenging element, this study attempts to draw inspirations from the Confucian pedagogy..